2014
DOI: 10.1371/journal.pone.0093655
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Androgen Receptor in Sex Determination in an Amphibian Species

Abstract: In mice and humans, the androgen receptor (AR) gene, located on the X chromosome, is not known to be involved in sex determination. In the Japanese frog Rana rugosa the AR is located on the sex chromosomes (X, Y, Z and W). Phylogenetic analysis shows that the AR on the X chromosome (X-AR) of the Korean R. rugosa is basal and segregates into two clusters: one containing W-AR of Japanese R. rugosa, the other containing Y-AR. AR expression is twice as high in ZZ (male) compared to ZW (female) embryos in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 26 publications
3
38
0
Order By: Relevance
“…In both species, SOX3 and AR are located on the sex chromosomes (Fujii et al 2014; Uno et al 2015). Interestingly, this inference extends even farther: orthologs of AR , SOX3 , and FMR1 are also present on the X chromosome of therian mammals, including humans (Uno et al 2013), and SOX3 is a new trigger for sex determination in a fish ( O. dancena ; Takehana et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In both species, SOX3 and AR are located on the sex chromosomes (Fujii et al 2014; Uno et al 2015). Interestingly, this inference extends even farther: orthologs of AR , SOX3 , and FMR1 are also present on the X chromosome of therian mammals, including humans (Uno et al 2013), and SOX3 is a new trigger for sex determination in a fish ( O. dancena ; Takehana et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Known sex-determining genes in vertebrates are usually homologs of genes involved in gonad differentiation (see, for example, Kikuchi and Hamaguchi, 2013;Bachtrog et al, 2014), and thus a better knowledge of the function of many genes in the ancestral mammalian X could allow the future identification of the sexdetermining gene in lacertids. Promising candidates might be genes homologous to Sox3 as in therian mammals and the fish Oryzias dancena (Takehana et al, 2014), or an androgen receptor, the alleles of which play a role in the sex determination of the Japanese frog Rana rugosa (Fujii et al, 2014). Candidates for the sex-determining gene in lacertids might also be found in the part of the lacertid Z chromosome homologous to GGA17.…”
Section: Identification Of Putative Z-specific Genesmentioning
confidence: 99%
“…Its expression is upregulated in the male gonad and was proposed as a candidate gene for testis differentiation [Yokoyama et al, 2009]. A recent study has shown that Ar is involved in male sex determination in G. rugosa [Fujii et al, 2014]. Indeed, a subset of transgenic female (ZW) frogs carrying an exogenous Z-Ar driven by the promoter region of both Z-Ar and Ef1α genes formed ovotestes.…”
Section: Importance Of Steroidsmentioning
confidence: 99%